'The Power of the Sack': The Cost of Job Loss in Canada, 1953-1985 - Grant, Hugh; Strain, Frank (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1990)
Abstract In this paper, we construct an index of the "cost of job loss" — defined as the income that a "representative worker" would lose upon being dismissed or laid off — in Canada between 1953 and 1985. Since this measure captures the monetary cost of unemployment, it is superior to the aggregate unemployment rate as an indicator of the relative bargaining power of capital and labour. Changes in the distribution of income between capital and labour are then considered. It is argued that with the decline in the cost of job loss between 1962 and 1973, the relative bargaining power of workers increased, and real wages rose accordingly. Subsequently, the cost of job loss has risen dramatically and real wages have fallen as capital has sought to restore conditions for rapid rates of accumulation.